Relevansi Etika Komunikasi Bagi Pemimpin Gereja - Adi Suhenra Sigiro; Putri Yulia Citra Br Berutu (International Forum of Researchers and Lecturers, 2024)
Everyone, including church leaders, must be able to understand and apply ethics in communication. By understanding ethics in communication, a leader knows the rules, norms and things that are good or not, as well as things that should be applied and not applied in communication so that the congregation served is able to receive and understand the messages received from the church leader. If church leaders do not have ethics in communicating, this will lead to failure in ministry. This research uses a literature study method, with a descriptive approach. Where the author will use books, journals and print media to dig up relevant information according to the research topic. Based on the research results, the relevance of communication ethics for church leaders is that church leaders know to apply the rules and norms in daily communication both with the congregation and with the community. The next relevance is that by understanding ethics in communication, a church leader knows the correct rules and regulations for delivering sermons to communicate God's word to the congregation. The next relevance or connection is that church leaders know the rules and norms when communicating with the congregation when conducting counseling.